Diagnostic Accuracy of Different Radiological Investigations in the Diagnosis of Perforated Duodenal Ulcer - Al marzooq, Tawfiq . j. Mohammad (AL-Kindy College Medical Journal, 2012)
Background; Perforated duodenal ulcer (PDU) is a common surgical emergency that is associated with high mortality and morbidity. Early diagnosis and prompt surgical treatment is required to prevent grave complications.Objective; The study was designed to evaluate the diagnostic accuracy of different radiological investigations in the diagnosis of perforated duodenal ulcer.Methods; A prospective study of 185 pts with PDU at al kindy teaching hospital, Baghdad, Iraq from June 2008- august 2010. patients were examined clinically and investigated by blood test, chest x ray, plain X ray of the abdomen. Ultrasonography (U/S) and CT scanning done for those patients with negative X- ray finding. Resuscitation by intravenous fluid and antibiotic done. Explorative laparotomy done for all patients, repair of perforation done by simple omental patch. Data regarding radiological, ultrasonographic and CT finding and operative finding were recorded.Results: The study of 185 pts with proven perforated DU revealed 162 (87.5%) male and 23 (12.5%) female with age ranging from 22-70 yrs ,the average was 38 years.Crescentic shape air under diaphragm was seen in chest or abdominal plain X ray in 121 (65.4%) pts and negative in 64 (34.6%) pts. For those 64 pts, a positive finding of free air or fluid was seen by U/S in 16 (25%) pts and positive CT finding was seen in 62 (96.9%) pts.The operative finding in those 64 pts were; a small perforation less than 0.5 cm in 24 pts, completely or partially sealed perforation in 19 pts, severe edema and narrowing of the pylorus in 15 pts and perforation larger than 1 cm but with little peritoneal soiling was seen in 6 pts.Conclusions: Pneumoperitonium was detected radiologically in 65% of pts of perforated DU. CT scan was found to be superior to U/S study for the diagnosis in pts with negative X-ray finding. For pts with perforated DU Conservative treatmentcan be adopted in pts with negative radiological findings.